Gagalkah TransJakarta? Kajian Kualitas Layanan pada Sistem Angkutan Cepat Massal TransJakarta - Fitriati, Rachma (Universitas Prasetiya Mulya, 2010)
The research aimed to study the busway users’ understanding, attitude, and behavior toward the quality of TransJakarta service, in order to provide alternative solution over the complexity of massive transportation problems in DKI Jakarta, as the capital city of Indonesia. In addition, the research presented some inputs to overcome the transportation problems in Jakarta that can be used as points of evaluation for other cities in Indonesia which have prepared or are preparing to make use of bus rapid transit system. The research was focused on the quality of TransJakarta service, and identified the necessary atributes to produce an optimum public service quality–as a part of social engineering study on massive transport system. The analysis used Service Quality (SERVQUAL) dan Importance-Performance Analysis (IPA) concepts, done through surveys on 450 respondents on eight busway corridors. The result showed that the users of TransJakarta value most the dimension of empathy and quite the reverse value worst the dimension of tangible. The data showed that empathy is the dimension in which service quality “is considered” most likely improved. While other dimensions, especially the dimensions of tangible, responsiveness and assurance ‘are considered’ already given, since the TransJakarta users regard them as being outside the management limit of Public Service Board of TransJakarta.